2016
DOI: 10.12816/0031222
|View full text |Cite
|
Sign up to set email alerts
|

The Musculoskeletal Manifestations of Type 2 Diabetes Mellitus in a Kashmiri Population

Abstract: Objectives: Diabetes mellitus (DM), is affecting an ever increasing number of people worldwide. Diabetes is associated with several musculoskeletal manifestations. These may involve, the upper as well as the lower limb. We conducted this study to find out the prevalence of musculoskeletal problems in type 2 diabetics in the Kashmiri population. Methodology:The study was conducted on 403 patients with diabetes and 300 controls. All patients underwent screening for any musculoskeletal abnormalities. The patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
2
14
1
1
Order By: Relevance
“…This may amplify the musculoskeletal signs and symptoms. 8 In this study, 78% cases had HbA1c >7. In study from Northwest India 14.6% study subjects had HbA1c ≤7.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…This may amplify the musculoskeletal signs and symptoms. 8 In this study, 78% cases had HbA1c >7. In study from Northwest India 14.6% study subjects had HbA1c ≤7.…”
Section: Discussionmentioning
confidence: 50%
“…While in study among Kashmiri population hand, elbow and shoulder were most commonly affected areas. 8 In this study the overall prevalence of musculoskeletal manifestations was 42%. While in study from Northwest India the prevalence was 57.01% and in a study of Kashmiri population 33% had musculoskeletal manifestations.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…All the studies done on diabetic complications in India have been reported from big cities. 4,5 This study was done at a rural medical college located in Chamba district of Bhat TA et al Int J Res Med Sci. 2019 Nov;7(11): [4237][4238][4239][4240][4241][4242] International Journal of Research in Medical Sciences | November 2019 | Vol 7 | Issue 11 Page 4238 Himachal Pradesh catering entirely rural population with limited health care facilities.…”
Section: Introductionmentioning
confidence: 99%
“…The chronic complication of Diabetes mellitus is a leading cause of death and disability. Type 2 diabetes mellitus (T2DM) is a multisystemic disease with development of additional manifestation such as musculoskeletal disorders (MSDs) [4]. The hyperglycemia in T2DM is the main cause of organ dysfunction like frozen shoulder (adhesive capsulitis), limited joint mobility (diabetic chieroarthropathy Dupuytren's contracture, carpel tunnel syndrome, flexor tenosynovitis (trigger finger), DISH (diffuse idiopathic skeletal hyperostosis), Charcot's joints, osteomyelitis, reflex sympathetic dystrophy, and diabetic amyotrophy [5].…”
Section: Introductionmentioning
confidence: 99%